Broad-scale impacts of salmon farms on temperate macroalgal assemblages on rocky reefs. Issue 1 (15th September 2015) - Oh, E.S.; Edgar, G.J.; Kirkpatrick, J.B.; Stuart-Smith, R.D.; Barrett, N.S.
Highlights: Nutrient impacts on benthic algae were investigated along gradients from fish farms. Detectable impacts extended between 100 m and 400 m distance from farms, on average. Macroalgal assemblages near farms were overgrown by epiphytes. Canopy-forming algae appeared unaffected by the organic richness gradient. Abstract: Intensive fish culture in open sea pens delivers large amounts of nutrients to coastal environments. Relative to particulate waste impacts, the ecological impacts of dissolved wastes are poorly known despite their potential to substantially affect nutrient-assimilating components of surrounding ecosystems. Broad-scale enrichment effects of salmonid farms on Tasmanian reef communities were assessed by comparing macroalgal cover at four fixed distances from active fish farm leases across 44 sites. Macroalgal assemblages differed significantly between sites immediately adjacent (100 m) to fish farms and reference sites at 5 km distance, while sites at 400 m and 1 km exhibited intermediate characteristics. Epiphyte cover varied consistently with fish farm impacts in both sheltered and exposed locations. The green algae Chaetomorpha spp. predominated near fish farms at swell-exposed sites, whereas filamentous green algae showed elevated densities near sheltered farms. Cover of canopy-forming perennial algae appeared unaffected by fish farm impacts.